EXPRESSIVE ILLOCUTIONARY SPEECH ACTS IN THE SUMMER I TURNED PRETTY TV SERIES - Panjaitan, Bella Natasia; Ambalegin, Ambalegin (Asosiasi dosen IDEBAHASA KEPRI, 2024)
This qualitative research aimed at finding out the speech acts and the functions of expressive illocutionary theorized by Searle & Vanderveken and Leech in conversations among characters in “The Summer I Turned Pretty” TV Series. The observational method and note-taking technique were employed to collect data. To analyze the data, the researchers used the pragmatic identity method. This research used a descriptive narrative method to present the results. Therefore, the results are presented in words and sentences. The findings of this research were of 13 different acts, and four different functions from 15 data. The researchers found there are 3 data of thank, 2 data of apologize, 1 data of greeting, 1 data of congratulate, 1 data of praise, 1 data of protest, 1 data of complaint, 1 data of lament, 1 data of deplore, 1 data of condole, 1 data of compliment, 1 data of boast, and 1 data of welcome. The most dominant act is the act of thank with 3 data. This is because the speakers and the hearers used to express gratitude. Based on the functions, there are 11 data of convivial, 2 data of conflictive, 1 data of collaborative, and 1 data of competitive found. The most dominant function of expressive act is convivial. This is because the speaker and the hearer show respect and politeness.